Navigating Crisis with Courage - Khondokar Sabera Hamid; Khan Md. Hasanuzzaman (Annals of the University of Craiova for Journalism, Communication and Management, 2025)
This qualitative study investigates how head teachers in Bangladesh's Lakshmipur primary schools demonstrated leadership both during and after the 2024 flash floods. Through semi-structured interviews with twelve teachers, Focus Group Discussions (FGDs) with twenty parents, and Key Informant Interviews (KIIs) with three head teachers, the study examines how head teachers handled school operations, responded to the crisis, protected student welfare, and promoted community cooperation. The results show that by implementing emergency response plans, gathering resources, offering psychosocial support, and maintaining educational continuity through creative and situation-specific methods, head teachers became recognized as community leaders. They provided vital insights into disaster-responsive educational leadership in vulnerable rural settings, and their leadership was marked by resilience, empathy, adaptability, and grassroots coordination. Head teachers used unofficial networks and community goodwill to restore education with low dropout rates in spite of health hazards, communication breakdowns, and infrastructure damage. The study emphasizes the potential of local leadership in promoting educational resilience and stresses the significance of incorporating school-based disaster management into national education policies. These observations add to the expanding corpus of research on crisis leadership in education, particularly in settings that are vulnerable to climate change.